Risk Mitigation in Higher Education Human Resource Management: A Proactive Approach to Academic Sustainability - Tewu, Denny; Bernadetha Nadeak; Hardiyanti, Nurul Rida; Napoleon Sinaga (International Journal of Economics (IJEC), 2025)
This study aims to identify and formulate a risk mitigation model for human resource management (HR) in Indonesian universities with a focus on academic sustainability. Using a qualitative approach and Grounded Theory, data were collected through in-depth interviews with key informants from various higher education institutions. The analysis process was conducted through the stages of open coding, axial coding, and selective coding to build a theoretical model based on the data. The results of this study indicate that universities in Indonesia face various structural and systemic HR risks, such as dependence on senior lecturers, weak regeneration and retention policies, and workload imbalances. Based on the findings, a risk-mitigation model was developed based on a proactive approach that includes succession planning, continuous training systems, work flexibility, and integration of risk management into institutional governance. This model has practical implications for the formulation of adaptive and long-term HR policies. This study contributes to the development of HR risk management theory in the higher education sector and provides a policy reference for educational institutions to improve academic resilience and sustainability. Further research is recommended to test this model in various types of institutions and in the context of digital transformation in higher education.